Aspirin Actions in Treatment of NSAID-Exacerbated Respiratory Disease - Sehanobish, Esha; Asad, Mohammad; Barbi, Mali; Porcelli, Steven A.; Jerschow, Elina (Frontiers in Immunology, 2021)
NSAID-exacerbated respiratory disease (N-ERD) is characterized by nasal polyposis, chronic rhinosinusitis, adult-onset asthma and hypersensitivity reactions to cyclooxygenase-1 (COX-1) inhibitors. Among the available treatments for this disease, a combination of endoscopic sinus surgery followed by aspirin desensitization and aspirin maintenance therapy has been an effective approach. Studies have shown that long-term aspirin maintenance therapy can reduce the rate of nasal polyp recurrence in patients with N-ERD. However, the exact mechanism by which aspirin can both trigger and suppress airway disease in N-ERD remains poorly understood. In this review, we summarize current knowledge of aspirin effects in N-ERD, cardiovascular disease, and cancer, and consider potential mechanistic pathways accounting for the effects of aspirin in N-ERD.